Enhancing Big Data Management Strategies For Small And Medium-Sized Enterprises In Delhi NCR: A Comparative Analysis (Journal of Namibian Studies : History Politics Culture, 2023)
This research study explores the Big Data Small and medium-sized businesses that have used a variety of management techniques (SMEs) in the Delhi National Capital Region (NCR) and aims to compare and evaluate their effectiveness in terms of business performance, operational efficiency and competitive advantage. The study utilizes descriptive statistics and regression analysis to analyze the data collected from a sample of SMEs in the region. The findings indicate significant variations in the effectiveness of different strategies, with Strategy A demonstrating positive impacts on business performance and operational efficiency, Strategy B showing stronger effects across all outcome variables, and Strategy C exhibiting a stronger association with competitive advantage. The study emphasizes the importance of strategic selection and implementation of big data management strategies for SMEs to enhance their competitiveness. Further research is recommended to explore additional factors influencing strategy effectiveness and provide specific recommendations for SMEs in optimizing their big data management practices.